HUBUNGAN DUKUNGAN SOSIAL GURU DENGAN PENYESUAIAN DIRI SISWA SMP DI PONDOK PESANTREN MUHAMMADIYAH BOARDING SCHOOL AL-AMIN BOJONEGORO - Nida'uz Zakiyah; Nur Ainy Fardana Nawangsari (Lafadz Jaya Publisher, 2024)
Junior high school students who are in Islamic boarding schools are vulnerable to experiencing personal adjustment problems. At that age, individuals are deal with the challenges of change and their developmental tasks. With strong support, it is hoped that it can help students in facing the challenges and personal adjustment at Islamic boarding schools. This study aims to determine the relationship between teacher social support and junior high school students' adjustment at the Muhammadiyah Islamic Boarding School Al-Amin Bojonegoro. This study uses a quantitative approach with survey research methods. The research subjects were junior high school students living in the Islamic boarding school MBS Al-Amin Bojonegoro, both male and female, totaling 157 people. The measuring tool used is The Child and Adolescent Social Support Scale (CASSS) developed by Demaray et al. (2010) and Student Adaptation to College Questionnaire (SACQ) developed by Baker et al. (1985). Both measuring tools have been adapted by researchers and adapted to the research context. The analysis technique in this study uses the Product Moment correlation technique from Pearson. The results of the analysis show that there is a positive and significant relationship (r = 0.463; p = 0.000) between teacher social support and junior high school students' adjustment at the Islamic boarding school MBS Al-Amin Bojonegoro. So the conclusion that can be taken from this study is that the higher the social support given, the higher the level of personal adjustment.